2019
DOI: 10.4110/in.2019.19.e16
|View full text |Cite
|
Sign up to set email alerts
|

p62 Negatively Regulates TLR4 Signaling via Functional Regulation of the TRAF6-ECSIT Complex

Abstract: Sequestosome 1 (SQSTM1, p62), a ubiquitin binding protein, plays a role in cell signaling, oxidative stress, and autophagy. However, its functional role in inflammatory signaling is controversial. Recent studies have shown that p62 is negatively implicated in inflammatory responses. But, the precise molecular mechanisms by which p62 regulates inflammatory responses remain unclear. In this study, we report on a new regulatory role for p62 in TLR4-mediated signaling. p62 overexpression led to the suppression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…These results indicated that p62 played a positive role in antiviral immune responses and a negative role in DTMUV replication. Recent reports show that p62 acts as a regulator of host immunity by its function as a cargo adaptor in selective autophagy process [52][53][54], whereas SQSTM1/p62 not only functions as a cargo adaptor in the autophagy pathway but also acts as a signaling hub that regulates various physiological processes such as NF-κB signal and antioxidant stress [19,55,56]. Our findings provided evidence of the function of p62 as a regulator of antiviral immune responses and indicated that p62 regulated not only the NF-κB signal but also the IRF7 signal.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that p62 played a positive role in antiviral immune responses and a negative role in DTMUV replication. Recent reports show that p62 acts as a regulator of host immunity by its function as a cargo adaptor in selective autophagy process [52][53][54], whereas SQSTM1/p62 not only functions as a cargo adaptor in the autophagy pathway but also acts as a signaling hub that regulates various physiological processes such as NF-κB signal and antioxidant stress [19,55,56]. Our findings provided evidence of the function of p62 as a regulator of antiviral immune responses and indicated that p62 regulated not only the NF-κB signal but also the IRF7 signal.…”
Section: Discussionmentioning
confidence: 99%
“…Although the regulatory role of p62 in inflammatory responses is controversial [9,10], it is thought to be involved in the induction of inflammatory cytokine production via TNF Tumor necrosis factor) receptor-associated factor 6 (TRAF6) polyubiquitination and, thereby, NF-κB activation [11,12]. A recent report has shown that p62 is negatively implicated in Toll-like receptor 4 (TLR4)-mediated signaling through inhibition of TRAF6-evolutionarily conserved signaling intermediate in Toll pathways (ECSIT) association and the ubiquitination of ECSIT by TRAF6 [13]. Importantly, p62 −/− KO mice exhibited a higher mortality rate following LPS challenge [13], suggesting that p62 might negatively regulate TLR4-mediated signaling for the activation of NF-κB.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report has shown that p62 is negatively implicated in Toll-like receptor 4 (TLR4)-mediated signaling through inhibition of TRAF6-evolutionarily conserved signaling intermediate in Toll pathways (ECSIT) association and the ubiquitination of ECSIT by TRAF6 [13]. Importantly, p62 −/− KO mice exhibited a higher mortality rate following LPS challenge [13], suggesting that p62 might negatively regulate TLR4-mediated signaling for the activation of NF-κB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting and IP assays were performed as previously described [13,15,16,[23][24][25][26][27][28][29][30][31]. Briefly, mock vector as control vector, MYC-TRAF6, FLAG-AMPKαl, and MYC-BECN1 were transfected into HEK293T cells using Lipofectamine 2000 for 38-48 h. Cell lysates were immunoprecipitated with anti-FLAG or anti-MYC antibody.…”
Section: Western Blotting Analysis and Immunoprecipitation (Ip) Assaysmentioning
confidence: 99%